FISH FARMERS ATTITUDE TOWARDS PRESENCE MINI PELLET MILLIN SEBERANG TALUK HILIR VILLAGE, KUANTAN TENGAH DISTRICT, KUANTAN SINGINGI REGENCY, RIAU PROVINCE - Reyza Pahlepi; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 1 to 7Octobert 2013 in the Seberang Taluk Hilir Village, Kuantan Tengah District, Kuantan Singingi Regency, Riau Province. This research purposed to investigate the characteristics of fish farmers, knew socio-economic conditions in the case of ownership of assets, knew the attitude of fish farmers. This research used survey method. Respondents in this research was fish farmers who use mini pellet mill of 15 people. The data collected was primary data and secondary data .From the social economy there are a lot of changes , such as changes in education,employment, income and asset ownership change. Results of farmers attitudes analysis of pricing was mostly good, namely 100,00%. Farmers attitude towards social assistance also showed a good attitude at 46,67%. Farmers attitude towardsawareness processing of the mill in protecting the environment showed a less favorable attitude at 53,30%.Key words : Attitude, Pellet mill, Aquaculture.